Changing the neurology policy landscape in the United States: Misconceptions and facts about epilepsy. Issue 7 (July 2018) - Grabowski, David C.; Fishman, Jesse; Wild, Imane; Lavin, Bruce
Highlights: Many clinical concepts about epilepsy rest on outdated theories and treatment approaches. Evidence is provided to dispel many misconceptions about epilepsy and its treatment. Evidence is provided informing health care providers and decision-makers on current epilepsy treatment. Abstract: Epilepsy has a relatively high prevalence, and diagnosis and treatment are often challenging. Seizure freedom without significant side effects is the ultimate goal for both physicians and patients, but not always achievable. In those cases, the treatment goals of patients and providers may differ. In the United States, many clinicians continue to prescribe older AEDs, even though newer AEDs have a more desirable safety and tolerability profile, fewer drug–drug interactions, and are associated with lower epilepsy-related hospital visits. Newer AEDs are more commonly prescribed by neurologists and epilepsy center physicians, highlighting the importance of access to specialty care. We report that antiepileptic drugs are not the dominant cost driver for patients with epilepsy and costs are considerably higher in patients with uncontrolled epilepsy. Poor drug adherence is considered a main cause of unsuccessful epilepsy treatment and is associated with increases in inpatient and emergency department admissions and related costs. Interventions and educational programs are needed to address the reasons for nonadherence. Coverage policies placing a higher cost burden on patients with epilepsy lead to lower treatment adherence, which can result in higher future health care spending. Epilepsy is lagging behind other neurological conditions in terms of funding and treatment innovation. Increased investment in epilepsy research may be particularly beneficial given current funding levels and the high prevalence of epilepsy.